THE EFFECT OF CAREER DEVELOPMENT AND ORGANIZATIONAL CULTURE WITH ORGANIZATIONAL COMMITMENT MEDIATION ON THE CIVIL SERVANTS’ PERFORMANCE AT THE OFFICE OF PUBLIC WORKS AND SPATIAL PLANNING OF BALI PROVINCE - Ni Wayan Nerowati; Ni Wayan Sitiari; I Made Sara (Universitas Warmadewa, 2018)
The objective of this study is to determine the influence of career development and organizational culture with organizational commitment as mediation on employee performance. This study was conducted at the Public Works Department of Bali Province with a number of sample is 74 people. Data were collected by using observation method and interview with based on questionnaire. Data were analyzed by using PLS analysis. The results showed that organizational culture had positive effect with insignificant on employee performance; organizational culture has a significant positive effect on organizational commitment; and organizational commitment significantly positive to employee performance. Career development negatively affects performance by not significant; career development has a positive effect on organizational commitment with no significant; organizational commitment mediates the influence of organizational culture on employee performance.